The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1939-165x.2009.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte counts in bronchoalveolar lavage fluid obtained from normal and Maedi–Visna‐infected sheep

Abstract: Cytologic examination of BALF is useful for the clinical diagnosis of Maedi in sheep and provides important information about the severity of the lung lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In the experiments conducted on mouse models which resulted in a study of various types of cells (macrophages, dendritic cells, T and B cells, neutrophils, and eosinophils), it was shown that in normal conditions, the number of macrophages relatively exceeds that of the other types of cells [2]. Coinciding experiments were conducted on other farm animals (sheep, cattle, goats, rabbits, pigs), and similar results were obtained [3,4,[9][10][11].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the experiments conducted on mouse models which resulted in a study of various types of cells (macrophages, dendritic cells, T and B cells, neutrophils, and eosinophils), it was shown that in normal conditions, the number of macrophages relatively exceeds that of the other types of cells [2]. Coinciding experiments were conducted on other farm animals (sheep, cattle, goats, rabbits, pigs), and similar results were obtained [3,4,[9][10][11].…”
Section: Introductionmentioning
confidence: 80%
“…Various diseases cause inflammatory responses in the lungs of domesticated animals. These vary among different species [3][4][5]. BAL is often used in medical practice but is being more or less applied in veterinary and scientific investigations [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cytological, microbiological, and immunological evaluation of BALF enables the detection of subclinical respiratory disease and the identification of the severity grade, and stage of inflammatory reactions in the respiratory tract [ 18 , 19 ]. BALF has been proven as a valuable sample for investigating tissue resident immune cells in the respiratory tract of several species including mankind [ 17 ], horses [ 20 ], cattle [ 21 , 22 ], sheep [ 23 ], alpaca [ 24 ], pigs [ 25 ], dogs [ 26 , 27 ], and cats [ 28 ]. Also in the dromedary camel, the BAL procedure has been recently used for the collection of samples for cytological analysis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%